Synergistic aerodynamic force assessment through an extended exergy approach - Mutangara, Ngonidzashe E. (Cranfield University, 2023)
Drag decomposition using energy and exergy-based methods has shown large utility for aerodynamic performance assessment through their flow-field decompositions into different physical mechanisms. A particularly significant advantage of these methods is their ability to identify recoverable energy, which describes the available energy imparted to the flow by the aircraft as it traverses through the fluid. This type of assessment is not possible with traditional momentum analysis. Thus, energy/exergy analysis uniquely evaluates the potential benefits of wake energy utilisation for thrust production through novel architectures such as boundary layer ingestion. The velocity decomposition approach has introduced notable improvements to this analysis framework. This allows for a phenomenological drag decomposition into reversible and irreversible components by splitting the velocity field into its isentropic and non-isentropic contributions within the flow. From this, the reversible drag originating from the bulk flow can be obtained through the isentropic field, whilst the non-isentropic field provides the irreversible dissipative drag arising from the boundary layer and wake zones. The work conducted in this thesis aims to improve the velocity decomposition approach by combining it with partial pressure field analysis, enabling the decomposition of pressure into Euler and dissipative parts, previously not achievable with velocity decomposition alone. Assessment in this manner improves the evaluation of recoverable energy by identifying the additional pressure work potential within the dissipative field. Additionally, the unification extends energy/exergy-based analysis principles to the near- field, providing a unique decomposition capable of evaluating the local accumulation of viscous drag through dissipative pressure and skin friction, whilst the induced drag is assessed from the non-dissipative pressure.
Sanders, Drewan S. - Associate Supervisor
Keywords: near-field; far-field; momentum; mechanical energy analysis; velocity decomposition; partial pressure fields; drag decomposition